Cost analysis of the Communication and Low Mood (CALM) randomised trial of behavioural therapy for stroke patients with aphasia. (January 2015) - Humphreys, Ioan; Thomas, Shirley; Phillips, Ceri; Lincoln, Nadina
Objective: To evaluate the cost effectiveness of a behavioural therapy intervention shown to be clinically effective in comparison with usual care for stroke patients with aphasia. Design: Randomised controlled trial with comparison of costs and calculation of incremental cost effectiveness ratio. Setting: Community. Participants: Participants identified as having low mood on either the Visual Analog Mood Scale sad item (≥50) or Stroke Aphasic Depression Questionnaire Hospital version 21 (SADQH21) (≥6) were recruited. Interventions: Participants were randomly allocated to behavioural therapy or usual care using internet-based randomisation generated in advance of the study by a clinical trials unit. Main measures: Outcomes were assessed at six months after randomisation, blind to group allocation. The costs were assessed from a service use questionnaire. Effectiveness was defined as the change in SADQH21 scores and a cost-effectiveness analysis was performed comparing the behavioural group with the usual care control group. The cost analysis was undertaken from the perspective of the UK NHS and Social Services. Results: The greatest difference was in home help costs where there was a saving of £56.20 in the intervention group compared to an increase of £61.40 in the control group. At six months the SADQH21 score for the intervention group was 17.3 compared to the control group value of 20.4. This resulted in a mean increase of 0.7 in the control group, compared to a mean significant different decrease of 6 in the intervention group ( P = 0.003). The Incremental Cost-Effectiveness Ratio indicated that the cost per point reduction on the SADQH21 was £263. Conclusion: Overall the behavioural therapy was found to improve mood and resulted in some encouraging savings in resource utilisation over the six months follow-up.